2022
DOI: 10.1038/s41419-022-04630-1
|View full text |Cite
|
Sign up to set email alerts
|

SF3B4 promotes ovarian cancer progression by regulating alternative splicing of RAD52

Abstract: Many studies have proven that splicing factors are crucial for human malignant tumor development. However, as a classical splicing factor, the expression of SF3B4 is not clear, and its biological function needs to be further clarified in ovarian cancer (OC). We determined that SF3B4 was obviously upregulated and its high expression was associated with poor prognosis in OC patients. In vitro and in vivo assays suggested that SF3B4 overexpression promoted OC cell proliferation and mobility, and downregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In recent years, more and more research has been conducted on SF3b4-related diseases such as Nagel syndrome and cancer [53]. Recently, Diao et al [54] found that SF3B4 promotes ovarian cancer progression by modulating alternative splicing of RAD52 [14]. SF3B4 is also closely related to the growth of non-small cell lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, more and more research has been conducted on SF3b4-related diseases such as Nagel syndrome and cancer [53]. Recently, Diao et al [54] found that SF3B4 promotes ovarian cancer progression by modulating alternative splicing of RAD52 [14]. SF3B4 is also closely related to the growth of non-small cell lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that SF3B4 plays important roles in the regulation of transcription, translation, and cell signaling in addition to pre-mRNA splicing. Importantly, emerging evidence suggests that the dysregulation of SF3B4 expression by gene mutations or other factors has been implicated in various diseases, including tumorigenesis and Nager syndrome (NS) [12][13][14]. For example, the upregulation of SF3B4 promotes tumorigenesis in hepatocellular carcinoma (HCC) [12], esophageal squamous cell carcinoma (ESCC) [13], and ovarian cancer (OC) [14], whereas its downregulation or depletion results in pancreatic cancer [15] and breast cancer in NS patient [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutated gene SF3B4 in Family 2, encodes one of the components of the splicing factor 3b (SF3b) complex 32. The loss or gain of function caused by SF3b4 mutations is frequently associated with aberrant cell development and plays a role in the pathogenesis of various cancers including hepatocellular carcinoma, ovarian cancer and oesophagus squamous cell carcinoma 33–36. Whether SF3B4 plays a role in SSC self-renewal, leading to selfish spermatogonial selection, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…32 The loss or gain of function caused by SF3b4 mutations is frequently associated with aberrant cell development and plays a role in the pathogenesis of various cancers including hepatocellular carcinoma, ovarian cancer and oesophagus squamous cell carcinoma. [33][34][35][36] Whether SF3B4 plays a role in SSC self-renewal, leading to selfish spermatogonial selection, requires further investigation. Specifically, all different types of recurrence risk can be directly assessed by obtaining mosaicism VAF results from sperm sequencing analysis.…”
Section: Mutation Originmentioning
confidence: 99%